Demand for Skills in Albania : An Analysis of the Skills Towards Employment and Productivity Survey - World Bank Group (World Bank, Washington, DC, 2018)
This report aims to provide policy makers in Albania with new evidence to inform the design and implementation of public policies on post-secondary education, vocational education and training (VET) system labor market information and intermediation, and labor policies. The STEP Employer Survey adds value to other ongoing efforts in Albania (e.g., by the Institute of Statistics in Albania [INSTAT], United Nations Development Programme [UNDP], and the National Employment Services [NES]) aimed at assessing occupational demand by focusing on: (i) the labor demand side – employers – which often tends to be disconnected from formal skills development systems; (ii) actual skills, rather than education levels, diplomas, or years of schooling as proxies for skills; and (iii) the broader set of skills, not just job-technical skills associated with one occupation or another. The findings of the report are expected to be relevant to inform public policies looking to narrow skills gaps, but also for firms, private and public education providers, and youth and adult job seekers looking to develop and reinforce labor market-relevant skills.